2012
DOI: 10.4103/0975-7406.100258
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of osseous lesion associated with palatoradicular groove using local drug delivery and guided tissue regeneration: A report of two cases

Abstract: Developmental grooves are not rare and often appear on maxillary lateral and central incisors and are an important predisposing factor to localized periodontal disease. Various techniques have been adopted to eliminate the groove and regenerate lost periodontium. This report of two cases describes the technique of using the local drug delivery system with chlorehexidine and the guided tissue regeneration (GTR) to control the disease progression and regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…These clinical trials have attested the safety and non-toxicity of the product reporting no serious adverse effects [17][18][19][20]. The clinical efficacy of this chip in reducing probing depth, bleeding on probing and clinical attachment loss has been reported [18][19][20][21]. To the best of our knowledge, the microbiological benefits of this chip have not been researched.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These clinical trials have attested the safety and non-toxicity of the product reporting no serious adverse effects [17][18][19][20]. The clinical efficacy of this chip in reducing probing depth, bleeding on probing and clinical attachment loss has been reported [18][19][20][21]. To the best of our knowledge, the microbiological benefits of this chip have not been researched.…”
Section: Discussionmentioning
confidence: 99%
“…Its coronal edge is known to degrade in 10 days. Its safety and efficacy in reducing probing depth and bleeding on probing has been tested in clinical trials [19][20][21][22]. An in vitro release profile of chlorhexidine of 1105µg at 24 hours to 40µg by 7 days has been noted which is however not similar to the release profile of Periochip [19,38].…”
Section: Discussionmentioning
confidence: 99%
“…[8] In the present case, for the regenerative procedure, the defect was filled with demineralized, freeze-dried bone graft and covered with resorbable membrane as there was less possibility of containing the blood coagulum during the healing period. [9] Apart from the fact that there is no need for a second surgical intervention for removal of the membrane, it's reported that bioabsorbable membranes present improved soft-tissue healing. [5] Due to these advantages we used a resorbable collagen membrane that have the ability to prevent the apical migration of epithelium along the root surface during periodontal wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Palato-radicular groove (PRG) is defined as an anomalous formation of teeth that begins in the central fossa of the maxillary incisors, extends over the cingulum, and continues apically to varying depths and distances of the root surface[ 1 ]. The etiology of PRGs remains unclear.…”
Section: Introductionmentioning
confidence: 99%